Molecular mechanisms underlying genotype‐dependent responses to dietary restriction. Issue 6 (11th August 2013) - Schleit, Jennifer; Johnson, Simon C.; Bennett, Christopher F.; Simko, Marissa; Trongtham, Natalie; Castanza, Anthony; Hsieh, Edward J.; Moller, Richard M.; Wasko, Brian M.; Delaney, Joe R.; Sutphin, George L.; Carr, Daniel; et al.
Summary Dietary restriction (DR) increases lifespan and attenuates age‐related phenotypes in many organisms; however, the effect of DR on longevity of individuals in genetically heterogeneous populations is not well characterized. Here, we describe a large‐scale effort to define molecular mechanisms that underlie genotype‐specific responses to DR. The effect of DR on lifespan was determined for 166 single gene deletion strains in Saccharomyces cerevisiae. Resulting changes in mean lifespan ranged from a reduction of 79% to an increase of 103%. Vacuolar pH homeostasis, superoxide dismutase activity, and mitochondrial proteostasis were found to be strong determinants of the response to DR. Proteomic analysis of cells deficient in prohibitins revealed induction of a mitochondrial unfolded protein response (mtUPR), which has not previously been described in yeast. Mitochondrial proteotoxic stress in prohibitin mutants was suppressed by DR via reduced cytoplasmic mRNA translation. A similar relationship between prohibitins, the mtUPR, and longevity was also observed in Caenorhabditis elegans. These observations define conserved molecular processes that underlie genotype‐dependent effects of DR that may be important modulators of DR in higher organisms.